Anti-inflammatory, immunomodulatory and anti-oxidant effects of Ocimum basilicum L. and its main constituents: A review - Elaheh Kamelnia; Reza Mohebbati; Reyhane Kamelnia; Hesham El-Seedi; Mohammad Hossein Boskabady (Iranian Journal of Basic Medical Sciences, 2023)
Ocimum basilicum L. (O. basilicum) is an ornamental and therapeutic plant with various pharmacological effects and medical applications. In this article, detailed information on the anti-oxidant, immunomodulatory, and anti-inﬂammatory properties of O. basilicum and its main constituents was provided. The literature survey of the different databases until the end of November 2021 was explored on the immunomodulatory, anti-inﬂammatory and anti-oxidant effects of the herb and its constituents. The plant and its constituents showed diverse pharmacological effects including immunomodulatory, anti-inflammatory and anti-oxidant properties by improving of the inflammatory mediators including interleukin (IL)-10, IL-4, tumor necrosis factor-alpha (TNF-α), interferon gamma (IFN-γ), nitric oxide (NO), serum levels of IFN-γ, IL10 and IL-4, IgG, IgM and phospholipase A2 (PLA2), immunoglobulin E (IgE), total protein (TP), oxidant and anti-oxidant markers. O. basilicum and its main constituents therefore, could be effective on the treatment of diseases associated with inflammation, immune dysregulation and oxidative stress. The present review article provides readers with organized information about the anti-oxidant, immunomodulatory, and anti-inﬂammatory properties of O. basilicum.